2021
DOI: 10.12998/wjcc.v9.i31.9535
|View full text |Cite
|
Sign up to set email alerts
|

Rapid response to radiotherapy in unresectable tracheal adenoid cystic carcinoma: A case report

Abstract: BACKGROUND Adenoid cystic carcinoma (ACC) occurs mainly in the head and neck. Tracheal ACC (TACC) is uncommon. Primary resection is recommended as the main treatment of choice, and radiotherapy is considered for residual disease in the postoperative setting. Definitive radiotherapy is an alternative approach to cure unresectable TACC. As the status of radiosensitivity in TACC is uncertain, the evidence for radiotherapy in unresectable TACC is not well established, especially in terms of the optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Similarly, in our study, disease extent was identi ed to be the primary reason for inoperability, with only 26.4% of the patients being eligible for surgery. Therefore, while RT has been considered a crucial curative treatment option for patients with unresectable tumors, its outcomes remain controversial and are often limited to small case series [11][12][13]. Our current study revealed a tendency towards improved PFS and OS when concurrent chemotherapy was administered alongside RT, indicating that CCRT may be an effective treatment option for patients who are not eligible for surgery.…”
Section: Discussionmentioning
confidence: 71%
“…Similarly, in our study, disease extent was identi ed to be the primary reason for inoperability, with only 26.4% of the patients being eligible for surgery. Therefore, while RT has been considered a crucial curative treatment option for patients with unresectable tumors, its outcomes remain controversial and are often limited to small case series [11][12][13]. Our current study revealed a tendency towards improved PFS and OS when concurrent chemotherapy was administered alongside RT, indicating that CCRT may be an effective treatment option for patients who are not eligible for surgery.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies showed that surgery was correlated to a significantly better survival than nonsurgical treatment, 3 , 9 , 10 demonstrated by an overall 5-year and 10-year survival rates, in case of resected tracheobronchial ACC, of 52% to 88.7% for R0 resections and 29% to 43.2% for R1 resections. In unresectable patients, the overall 5-year and 10-year survival rates were 33% and 10%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Adjuvant radiotherapy is currently used when positive margins (R1 or R2, grossly positive margins) are found at histologic examination. 10 , 12 , 13 , 14 Patients with grossly positive airway margins had significantly worse survival than patients with grossly negative resection margins. 11 , 12 In 1996, Regnard and colleagues 15 published a multi-institutional French study in which complete or incomplete resection for ACC was associated with a 5-year survival of 82% (36 patients) and 63% (26 patients), respectively.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Regarding advanced inoperable ACCL, palliative chemotherapy and radiotherapy should be considered as an alternative therapy (23,33,34). Wu et al reported a case with unresectable tracheal ACC who responded rapidly to radiotherapy (35). Moreover, only a few case reports have indicated that ACCL patients may be candidates for target therapy (36).…”
Section: E V E N F O R S a C C L F R O M T H E H E A D A N D N E C K ...mentioning
confidence: 99%